1989
DOI: 10.1557/jmr.1989.0557
|View full text |Cite
|
Sign up to set email alerts
|

The melting point depression of tin in mechanically milled tin and germanium powder mixtures

Abstract: A melting point depression, δTM, has been observed for Sn in Ge/Sn (50 at.% Sn) dispersions which were prepared by mechanical milling of Ge and Sn powders. Sn and Ge are immiscible and form a fine dispersion of the pure components when milled in a high energy ball mill. The magnitude of δTM, as measured by DSC, increases with milling time, i.e., with refinement of the dispersion. Melting is observed to begin as low as 36 °C below the equilibrium bulk melting temperature. The magnitude of δTM is reduced by abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The Sn particle sizes of the as-milled samples were calculated to be 44, 41, 39 and 37 nm for the powders milled after 1, 2, 3 and 4hr, respectively. These results are the characteristic feature of BM and consistent with the findings in the literature [1][2][3][4].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The Sn particle sizes of the as-milled samples were calculated to be 44, 41, 39 and 37 nm for the powders milled after 1, 2, 3 and 4hr, respectively. These results are the characteristic feature of BM and consistent with the findings in the literature [1][2][3][4].…”
Section: Resultssupporting
confidence: 92%
“…It is suggested that abundant stored energy forms during ball milling due to the introduction of many dislocations. For instance, Koch et al [1] corroborated that ball milling of Sn and Ga particles can produce significant amounts of stored energy and further influence the melting behavior of Sn. Previous work using a lower weight ratio (1/3) of SnO 2 /Al powders also showed analogous effect [12], where both exothermic and endothermic reactions occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melting point depressions in immiscible nanophase systems have also been found in the case where the melting phase is the matrix in which inert particles are embedded. An example is found in ballmilled Sn/Ge mixtures [28,29] ip; which the Ge particles are about 10 nm in diameter, dispersed in the Sn; the melting point of the Sn is depressed by as much as 40 K. The depression cannot be explained using eq. (13) as the interface curvature is not readily defined.…”
Section: Depression Of Melting Pointmentioning
confidence: 99%